2021
DOI: 10.1021/acs.oprd.1c00102
|View full text |Cite
|
Sign up to set email alerts
|

A Continuous-Flow Electrochemical Taylor Vortex Reactor: A Laboratory-Scale High-Throughput Flow Reactor with Enhanced Mixing for Scalable Electrosynthesis

Abstract: We report the development of a small footprint continuous electrochemical Taylor vortex reactor capable of processing kilogram quantities of material per day. This report builds upon our previous development of a scalable photochemical Taylor vortex reactor (Org. Process Res. Dev. 2017, 21, 1042; 2020, 24, 201–206). It describes a static and rotating electrode system that allows for enhanced mixing within the annular gap between the electrodes. We demonstrate that the size of the annular gap and the rotation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…A schematic of the reactor is depicted in Figure 2 , and a full piping diagram showing the overall setup is detailed in the Supporting Information. Unpublished experiments to measure the residence time distribution in our original electrochemical Taylor vortex reactor with a carbon outer electrode 51 indicated that the mean residence time was only slightly longer than the value estimated by dividing the reactor volume by the volumetric flow rate. The lengthening of the time may well be due to the adsorption of the Rose Bengal dye used in the experiment to the porous carbon electrode.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…A schematic of the reactor is depicted in Figure 2 , and a full piping diagram showing the overall setup is detailed in the Supporting Information. Unpublished experiments to measure the residence time distribution in our original electrochemical Taylor vortex reactor with a carbon outer electrode 51 indicated that the mean residence time was only slightly longer than the value estimated by dividing the reactor volume by the volumetric flow rate. The lengthening of the time may well be due to the adsorption of the Rose Bengal dye used in the experiment to the porous carbon electrode.…”
Section: Resultsmentioning
confidence: 83%
“…Our original report, 51 focused on electrochemical oxidation, used a graphite tube as the outer anode of the reactor. Here, however, as a sacrificial anode is required for this type of reduction reaction, other materials were considered for the electrodes; indeed, when the reduction reaction was run with the graphite anode, no reaction took place.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations